The relationship between primordial sentiments and the political aspirations of Sabah’s Youth - Abang Mohd. Razif Abang Muis; Yusten Karulus; Lai yew meng (Knowledge Words Publications, 2025)
This study identifies the relationship between primordial sentiments and political aspirations among youths in the state of Sabah. Primordial sentiment refers to individuals’ attachment to basic identities such as ethnicity, religion, language and locality, which commonly shape their political orientation and inclinations. Sabah, as a state rich in ethnic diversity and with a complex political history, provides an important context for examining how these identity factors influence the formation of political aspirations among the younger generation. The study adopted a quantitative approach through a survey method, involving 4,519 youths selected via stratified random sampling across the state’s five main administrative divisions. The constructed questionnaire instrument was analyses using SPSS software. The analysis results show a significant relationship between primordial sentiment and political aspirations, particularly in the dimensions of ethnic and regional attachment. These findings have important implications for the need to formulate political policies that are more inclusive and contextual, in line with the diverse local identities among Sabah’s youth.